IMPLEMENTASI GAP ANALISIS PADA PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN PENILAIAN UNTUK EVALUASI KINERJA DOSEN - Herlina (LP2M CBI PRESS, 2016)
Lecturers’ good performance will influence the increase of their students’ quality. That’s why, It is very important for a higher education to make appraisal of lecturers’performance. AMIK CBI by the head of study program has done the appraisal by using Sasaran Kinerja Individu (SKI). The components of the appraisal consisted of Academic Performance and Consumer Service, and Individual Performance. Head of study program had a high expectation on lecturers’ performance in each indicator included in the SKI, but the fact showed that not all lecturers were able to achieve the expectation. The gap happened if there were differences between the expectation toward lecturers with the score achieved by the lecturers in the SKI. Deccission Support System by using Gap method was made based on aspects in the SKI. The process of counting the gap was done to see lecturers’ rank who had a better achievement. The application was made by using SQL data base and PHP as the tools.